Quality Seed Cane Production of Sugarcane(Saccharum spp. hybrid complex) through Bud Chip Technology for Replacement of Old Varieties in West Bengal. - Mahata, Goutam (Indian Farming, 2022)
Sugarcane (Saccharum spp. hybrid complex), having religious value is being cultivated in West Bengal for a long time. Traditional varieties are cultivated (3-budded setts) using conventional methods mainly due to unavailability of quality seed cane of newly released varieties and transportation cost of huge seed materials, required for planting (6 t/ha). Sugarcane Research Station, Bethuadahari, Nadia is the only source of quality seed cane of newly released varieties in West Bengal. The performance of the only one operational sugar mill, Khaitan (India) Ltd. at Plassey, Nadia in West Bengal have very poor recovery record as compared to national average. The main problem for implementation of sustainable development of sugarcane based cropping system in West Bengal is transportation of quality seed cane to different districts. Quality seed cane lifted from the research station from different districts was 454.5 quintal and 174.0 quintal during 2016–17 and 2017–18 respectively, clearly indicate the declining trend of seed cane supply. In this context, sugarcane bud chip technology plays an important role on quality seed production and fast replacement of old varieties. This is a low cost technology with high seed multiplication ratio, 6–8 weeks’ time saving and is reliable by eliminating about 80–90% seed cane to manageable bud chips making transport and handling easy.